The deterioration of current account balance in selected countries of MENA: Causes of concern - Badwan, Nemer; Al-Qubbaj, Ihab (Asian Journal of Economics and Empirical Research, 2024)
The purpose of this paper is to analyze the macroeconomic factors that influence the current account balance deterioration in the selected Middle East and North Africa MENA countries (Iran, Iraq, Jordan, Syria, Palestine, and Lebanon). Data from six MENA countries were analyzed using a panel-static approach. This study employs the Breusch-Pagan Lagrangian multiplier test, the pooled ordinary least squares model (OLS), and the random effect model (REM). The findings reveal that exchange rate (ER), interest rate (IR), and term of trade (ToT) are the main factors that influence the deterioration of the current account balance. The money supply (MS) and oil prices (OP) had negligible correlations with the current account balance. The study's findings suggest significant practical implications for policymakers and regulators in MENA countries. Given the significant influence of exchange rate (ER), interest rate (IR), and term of trade (ToT) on the current account balance, we recommend that the authorities in MENA countries implement policy reforms and macroeconomic adjustments to mitigate the current account balance deterioration. A deterioration in the current account balance began in 2018, sparking concerns in most MENA countries. The problem in the current account has led to various disadvantages in MENA countries, which will harm the economic health of the countries.